2021
DOI: 10.3390/ijerph18136860
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Ambient NO2 Increases the Risk of Dry Eye Syndrome in Females: An 11-Year Population-Based Study

Abstract: Previous studies have indicated that women suffer from dry eye syndrome (DES) more significantly than men. Therefore, we specifically explore the associations between air pollutant levels and the risks of DES for women. The study obtained 27,605 participants from the 29 recruitment centers of the Taiwan Biobank, which was established in October 2012. A large scale cross-sectional study involving DES sufferers and age- and education-matched control groups without DES was designed. Based on the municipality of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It was further reported that O 3 upregulated the expression of IL-1β, IL-6, and IL-17 in tears and downregulated conjunctival goblet cell density in mouse models, leading to ocular surface discomfort and in ammation 30 . NO 2 exposure was positively correlated with DED outpatient visits 31 and increased risk of DED 32 . Higher NO 2 exposure was negatively correlated with tear secretion and TBUT and positively correlated with increased IL-6 and IL-8 expression in tears and aggravated MG dysfunction 17,19,31,33 .…”
Section: Discussionmentioning
confidence: 93%
“…It was further reported that O 3 upregulated the expression of IL-1β, IL-6, and IL-17 in tears and downregulated conjunctival goblet cell density in mouse models, leading to ocular surface discomfort and in ammation 30 . NO 2 exposure was positively correlated with DED outpatient visits 31 and increased risk of DED 32 . Higher NO 2 exposure was negatively correlated with tear secretion and TBUT and positively correlated with increased IL-6 and IL-8 expression in tears and aggravated MG dysfunction 17,19,31,33 .…”
Section: Discussionmentioning
confidence: 93%
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
“…Severe dryness of the mucosal surface in eyes and oral cavity were the primary clinical manifestation among SS patients, and the patients with SS who were exposed to air pollution was associated with more severe abnormalities of the ocular surface and eye irritation ( 22 ). In addition, environmental NO 2 concentration was proved to be associated with dry eye syndrome ( 23 ). This might support our results that exposure to NO 2 was associated with an increased risk of daily hospitalizations for SS.…”
Section: Discussionmentioning
confidence: 99%